Sustainable Agricultural Development through Community Service Programs in Gintung Village, Sukadiri District, Tangerang Regency - Muhammad Rizal Miftahul Fajri; Ahmad Bahrul Hikam (International Research & Development for Human Beings (IRDH), 2025)
This program was implemented in Gintung Village, Sukadiri District, Tangerang Regency, with the aim of developing a sustainable agricultural system to encourage local economic independence. Gintung Village, where the majority of residents are farmers, still practices conventional farming systems with a heavy reliance on chemical fertilizers and pesticides. This condition has the potential to reduce land fertility and negatively impact the environment. Using a participatory, education-based approach, this activity was carried out in the form of seminars and open discussions with farmers and community leaders. The seminars focused on increasing understanding of sustainable agricultural practices, the use of organic fertilizers, wise natural resource management, and community-based marketing strategies. The results of the activity showed an increase in farmer knowledge, the formation of organic farmer group initiatives, and the creation of direct distribution channels between farmers and local consumers. This program not only increases land productivity in an environmentally friendly manner but also strengthens the village economy through collaboration. Going forward, this activity model has the potential to be replicated in other areas with similar characteristics.